Integrating behaviour change counselling into chronic disease management: a square peg in a round hole? A system-level exploration in primary health care. (October 2019) - Vallis, M.; Lee-Baggley, D.; Sampalli, T.; Shepard, D.; McIssaac, L.; Ryer, A.; Ryan-Carson, S.; Manley, S.
Abstract: Objectives: The objective of this study is to evaluate the uptake of competency-based behaviour change counselling training within a primary healthcare setting. Specific questions concerning provider readiness for training, perceived importance of training in the context of service demands and perceptions of competence after training were addressed. Study design: A process-focused study which adopted a complex systems approach to implementation. Each step was evaluated before the next step was developed. The design was guided by the RE-AIM (reach, effectiveness, adoption, implementation, maintenance) framework. Methods: Four specific primary care services were identified and behaviour change counselling training tailored to each service was provided, based on a model of training built around competencies in establishing change-based relationships, assessing and promoting readiness to change, using evidence-based behaviour modification skills when ready and addressing psychosocial determinants of behaviour within scope of practice. Before training, a manager's readiness to facilitate training and identification of peer leaders to support ongoing practice of skills were completed. Results: Two programs negotiated 8 h of formal training, one program received 10 h and one program received 12 h. All programs engaged in peer support activities. Despite willingness to support training, 90% of managers were ambivalent about training activities, relative to one half of healthcare providers (HCPs). Few HCPs and no managers self-identified as ready without ambivalence. Furthermore, HCPs were reluctant to be evaluated by an expert and preferred self-evaluation methods. In contrast, HCPs uniformly endorsed the relevance, value and professional commitment to all component skills of the behaviour change counselling model. At the end of the training, over 75% of staff reported receiving formal training (reach). Almost 80% of staff reported using change-based relationship skills daily, with less frequent use of skills associated with addressing psychosocial issues. The degree of corrective feedback was generally low, however. An index of competency based on formal training, frequent use and receiving corrective feedback indicated that most HCPs did not meet these criteria. Conclusion: Training in behaviour change counselling competencies was successfully implemented in this project. The vast majority of HCPs received training, despite ambivalence. Furthermore, HCPs strongly valued these skills and used them frequently. However, they were reluctant to accept corrective feedback. Future research is needed to evaluate innovative strategies to overcome obstacles to receiving corrective feedback in the use of behaviour change counselling skills. Highlights: Behaviour change improves health outcomes but healthcare providers are not trained in behaviour change counselling. Using the RE-AIM framework we evaluated a service level behaviour change counselling training program in primary care. Healthcare providers and managers valued behaviour change counselling skills but were ambivalent about receiving training. Training reached most providers and many skills were used daily after training but few providers sought corrective feedback.